Deposition of Gold Nanoparticles on a Self‐Supporting Carbon Foil. (12th September 2022) - Hepperle, Philine; Baek, Woon Yong; Nettelbeck, Heidi; Rabus, Hans
Abstract: Electron emission cross sections of gold nanoparticles (AuNPs) are important for assessing their radiosensitizing effects from ionizing radiation using Monte Carlo simulations. Measurements of these data require samples of sufficiently large area density, homogeneous nanoparticle distribution, and a mechanically stable sample holder to ensure a low background signal. While several methods exist for the deposition of nanoparticles, there is little information regarding the deposition of AuNPs in an aqueous solution onto a self‐supporting film. The aim of this is to find suitable preparation techniques for AuNP samples which fulfill the above requirements. AuNP samples are produced using different deposition techniques and a 50 nm‐thick carbon foil as the substrate. These samples are characterized with respect to the size and spatial distribution of AuNPs using a scanning electron microscope. The drop‐casting technique yields the best results, while those obtained with the spin‐coater technique are less reproducible regarding sample stability. The microdrop method is deemed unsuitable due to its tendency to form AuNP clusters. Measurements conducted with a synchrotron radiation source, as well as with protons and electrons, confirm the suitability of these samples for studying electron emission spectra of AuNPs for different radiation types. Abstract : The deposition of gold nanoparticles on a self‐supporting carbon foil as a substrate presents several challenges. Different deposition techniques are tested for homogeneity of the nanoparticle distribution, a sufficiently high area density as well as mechanical stability. Samples are characterized using a scanning electron microscope to determine the size, shape, and local distribution.